Assessment of the general public's knowledge of atrial fibrillation through social media: a cross-sectional study - Brigitte FY Woo; Jeroen M Hendriks; Wilson Tam; Toon Wei Lim (BMC, 2023)
Abstract Background Early detection and timely treatment of atrial fibrillation (AF) remains pivotal to preventing AF-related complications. Public involvement in recognising potential AF symptoms and managing AF is vital for early detection and treatment of AF. Objective The aim of the study is to assess the general public's knowledge of AF using an online survey, disseminated via social media. Methods A cross-sectional online survey of the general public was conducted between November to December 2021. The survey's URL was shared on National University Heart Centre, Singapore's official Facebook page. Digital marketing strategies were employed to recruit members of the public. The 27-item survey assessed public's knowledge across five domains: basic information about AF, risk factors of AF, detection of AF, prevention of AF, and management of AF. Results The survey involved 620 participants. Approximately two-thirds were between the ages 21 to 40 years (64.5%), female (60%) and had at least a degree (64.7%) as their highest level of education. Participants obtained a mean percentage score of 63.3 ± 26.0 for their AF knowledge. One-way ANOVA was done to examine the associations between the participants' characteristics and their knowledge of AF. There were no statistically significant differences in the AF knowledge scores across the various sociodemographic subgroups. Conclusions Members of the public recruited from Facebook and via digital marketing had moderately good knowledge of AF. However, public awareness pertaining to preventing AF has potential for improvement. The utility of social media in reaching the general public was illustrated through this study.